Mountain tourism impact on bird diversity along hiking trails of Mount Prau, Central Java, Indonesia - MUHAMMAD ABDULLAH; LUCHMAN HAKIM; DIAN SISWANTO; DEWI LIESNOOR SETYOWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Abdullah M, Hakim L, Siswanto D, Setyowati DL. 2024. Mountain tourism impact on bird diversity along hiking trails of Mount Prau, Central Java, Indonesia. Biodiversitas 25: 4690-4698. Hiking represents a significant dimension of mountain tourism and has gained considerable popularity among travelers. Unfortunately, the perception of hiking activities as a form of mass tourism raises significant concerns regarding potential environmental degradation and the threats posed to biodiversity in mountainous regions. Birds are organisms that are sensitive to human activities. Therefore, a critical component for assessing the impact of mountain tourism on biodiversity is to analyze the diversity of bird species on several hiking trails. This study aims to examine the differences in bird species diversity on several hiking trails with different visitor frequencies on Mount Prau, Indonesia. Surveys for bird observations were conducted systematically using the Variable Circular Plot (VCP) method along the hiking trail. Bird species diversity data were analyzed to obtain Margalef's species richness index, Shannon diversity index, and Pielou's evenness index. In addition, correspondence analysis was also used to see the differences in the composition of bird community species on different hiking trails. Trails with high visitor preferences showed lower species richness, diversity, and evenness indices than rarely visited trails. Ordination analysis showed a clear grouping of bird communities based on species composition between highly visited and less visited routes. Less frequented Mount Prau trails host diverse endemics and high conservation status birds, while heavily frequented trails show reduced diversity. This finding confirms the negative impact of mountain tourism on bird biodiversity in the mountain area. This also signifies the need for a conservation strategy to balance mountain tourism with biodiversity conservation in Mount Prau. It should be able to limit the number of visitors, control access in sensitive areas, and involve methods of ecotourism that would favor wildlife.